Penilaian Kesehatan KSP Pinjam Bhakti Abadi Sesuai Peraturan Menteri Koperasi & UKM Nomor 09 Tahun 2020 - Nurizzah Salsa Alafia; Syamsul Bahri; Indah Dewi Nurhayati (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
This research aims to determine the health level of the Bhakti Abadi Savings and Loans Cooperative (KSP) for the 2022 financial year based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 09 of 2020 which concerns aspects of governance, risk profile, financial performance and capital. This research is a type of descriptive quantitative research. The subject of this research is the Bhakti Abadi Malang Savings and Loans Cooperative, where the object of evaluation is the health of KSP Bhakti Abadi. The data analysis technique in this research uses descriptive analysis. In this research, data was collected through observation, interviews and documentation methods. The research results show that the health level of KSP Bhakti Abadi Malang for the 2022 financial year is in the quite healthy category with an average score of 82.435 with details: (1) the governance aspect on average gets a score of 27.78 and is in the healthy category; (2) the risk profile aspect has an average score of 13.035 and is in the healthy category; (3) the financial performance aspect received an average score of 29.44 and was in the quite healthy category; (4) the capital aspect received an average score of 12.18 and was in the healthy category.